2018
DOI: 10.15625/0866-7187/40/2/11090
|View full text |Cite
|
Sign up to set email alerts
|

Soil structure and soil organic matter in water-stable aggregates under different application rates of biochar

Abstract: The effects of biochar and biochar combined with N-fertilizer on the content of soil organic matter in water-stable aggregates were investigated. A field experiment was conducted with different biochar application rates: B0 control (0 t ha-1), B10 (10 t ha-1) and B20 (20 t ha-1) and 0 (no N), 1st and 2nd levels of nitrogen fertilization on silt loam Haplic Luvisol (Dolna Malanta, Slovakia), in 2014. The N doses of level 1 were calculated on required average crop production using balance method. Level 2 include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The increases in grain yield of low chemical fertilizers substitute rates treatments might be due to the positive effects of organic manure and biofertilizers on wheat plants. As previously reported, organic manure amendment had the advantages of slowly releasing nutrients and preventing losses due to leaching [39,40] while biofertilizers could produce vitamins and substances that were beneficial to root development [32,41], which can promote wheat plants to absorb more nutrients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increases in grain yield of low chemical fertilizers substitute rates treatments might be due to the positive effects of organic manure and biofertilizers on wheat plants. As previously reported, organic manure amendment had the advantages of slowly releasing nutrients and preventing losses due to leaching [39,40] while biofertilizers could produce vitamins and substances that were beneficial to root development [32,41], which can promote wheat plants to absorb more nutrients.…”
Section: Discussionmentioning
confidence: 98%
“…Research [25,26] reported that the wheat grain yields were comparable in the treatments that received 80 t ha −1 yr −1 of organic manure or 204-252 kg N ha −1 yr −1 chemical N-fertilizers. As for biofertilizers, [27][28][29] reported that application of one biofertilizers obtained from sewage sludge at 7.2 L ha −1 increased maize grain yield by 17% compared with the untreated control and [10,30,31] revealed that biofertilizers amendments reduced inorganic N-fertilizers by 25% without decreasing rice yield in India [32].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in SOC was also found in the soil of the plots where biochar was applied in combination with N fertilizer, but the nitrogen application rate was found to limit C accumulation in the soil [32,33]. Significant differences in labile C content were observed in fractions of water-stable aggregates as a result of biochar application [36][37][38]. The highest biochar and fertilizer application rates significantly increased total C content in water-stable aggregates throughout the duration of the experiment [36,38].…”
Section: Published Outputs From the Biochar Experiments In Slovakiamentioning
confidence: 99%
“…Significant differences in labile C content were observed in fractions of water-stable aggregates as a result of biochar application [36][37][38]. The highest biochar and fertilizer application rates significantly increased total C content in water-stable aggregates throughout the duration of the experiment [36,38]. In addition to the standard soil organic matter parameters, the focus has also been on the calculation of C indexes that more precisely reflect changes in soil organic matter composition resulting from land management changes (e.g., after biochar application) [33].…”
Section: Published Outputs From the Biochar Experiments In Slovakiamentioning
confidence: 99%
See 1 more Smart Citation